Deep inspiratory breath‐hold radiotherapy for left‐sided breast cancer: Initial experience with Active Breathing Coordinator™ in a regional hospital. Issue 4 (23rd May 2022) - Kim, Bomi; Little, David; Groen, Julie; Yi, Ma; James, Melissa
Abstract: Introduction: Deep inspiratory breath‐hold (DIBH) has become standard in radiotherapy for left‐sided breast cancer to reduce the heart dose. This study evaluated breath‐hold stability and reproducibility using Elekta's Active Breathing Coordinator™ (ABC) and its effectiveness and feasibility in left‐sided breast cancer patients undergoing radiotherapy. Methods: Eligible patients were planned with free breathing (FB) and DIBH protocols. DIBH treatment was considered if the mean heart dose (MHD) was ≥2 Gy on the FB plan. Those who proceeded with DIBH treatment were enrolled for the pilot study. Electronic portal images of DIBH treatment beams were taken using the movie‐exposure mode for breath‐hold stability and reproducibility analysis. DIBH effectiveness in heart dose reduction and impact on simulation and treatment durations were compared with FB protocol. Results: Out of 56 eligible patients, 15 proceeded with DIBH treatment. The mean difference of patient setup within a single breath‐hold was 0.4 mm; between different breath‐holds of the same beam 1.1 mm and between different days 2.6 mm. DIBH reduced the MHD by 47% and the mean left anterior descending artery (LAD) dose by 35%. DIBH took longer time than FB in simulation and treatment. At least 14% of the eligible patients did not tolerate DIBH during simulation. Conclusions: ABC leads to stable and reproducible breath‐holds and results in significant heart dose reductions. It may not be tolerated by all patients and has resource implications. Abstract : Deep inspiratory breath‐hold using the Elekta Active Breathing Coordinator™ leads to stable and reproducible breath‐holds and results in significant heart dose reductions. It may not be tolerated by all patients and has resource implications.